2014
DOI: 10.1007/s00247-014-2876-5
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular capillary-type hemangioma: radiologic–pathologic correlation

Abstract: Intramuscular capillary-type hemangioma is a rare benign vascular tumor of skeletal muscle. The most typical imaging features show a heterogeneous intramuscular mass with fast flow, and intralesional fat. Although the lesion is relatively stable in appearance over time, imaging does not obviate the need for a biopsy to rule out sarcoma. The diagnosis can usually be established by typical findings on histopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…The histopathological features seen in our cases with atypical MRI findings are similar to those recently described in intramuscular capillary-type hemangiomas [7], which also demonstrate aggregates and sheets of small vessels lined by plump endothelial cells that splay apart individual muscle fibers. However, not all of our cases were primarily intramuscular, and in some cases the distortion of connective tissue elements seen on histological analysis was due to interstitial edema, rather than to vascular infiltration.…”
Section: Discussionsupporting
confidence: 85%
“…The histopathological features seen in our cases with atypical MRI findings are similar to those recently described in intramuscular capillary-type hemangiomas [7], which also demonstrate aggregates and sheets of small vessels lined by plump endothelial cells that splay apart individual muscle fibers. However, not all of our cases were primarily intramuscular, and in some cases the distortion of connective tissue elements seen on histological analysis was due to interstitial edema, rather than to vascular infiltration.…”
Section: Discussionsupporting
confidence: 85%
“…On radiographic images, they show a well-defined mass in the majority of patients13. Arteriovenous shunting and phlebolith are unusual in vascular tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have recently suggested that vascular malformations should be distinguished from hemangiomas10111213. In 1982, Mulliken and Glowacki proposed a simple classification system of vascular anomalies—hemangiomas versus vascular malformations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GLUT‐1 immunostain is positive in IH and negative in CH . ICTH, constitutes a distinct entity comprising a vascular benign tumor of skeletal muscle that can be histopathogically distinguished from the more common vascular anomalies . Patients present with a discrete, palpable, noncompressible mass located in an extremity.…”
Section: Discussionmentioning
confidence: 99%